Advances in Building Dye-Sensitized Solar Cells in Ecuador - Ramírez-Pérez, Javier (2013)
The fundamental requirement of any solar to electric conversion system is the absorption of a significant part of the incident solar radiation with a consequence utilization of the energy of the photons in an electrical process. There have been three generations of phovoltaic technologies. First generation solar cells build on single crystalline silicon wafers and consist of large area,single p-n junction diodes which can achieve very high efficiency-close to the theoretical efficiency of 33%-although the their production costs are very expensive. Second generation solar cells, represented by thin-film devices based on cadmium telluride (CdTe),copper, indium gallium selenide (CIGS),amorphous silicon and micromorphous silicon, require lower energy and production costs. Unfortunately, they suffer from much reduced energy conversion efficiencies compared to the first generation compared to the first generation because of the defects inherent in the lower-quality processing methods.Third generation solar cell technologies aim to increase the efficiency of the second generation solar cells while maintaining low production costs.